Implementation of Law Number 16 of 2019 Concerning Marriage Dispensation at the Kua of Mejayan District, Madiun Regency, Islamic Law Perspective - Januri, Januri; Kadenun, Kadenun; Ayu, Diyan Putri (Rechtsvinding, 2023)
Marriage dispensation at the Mejayan Religious Affairs Office increased from 10 to 185 people in one year, indicating an urgent need for guidance and support for married couples, both newlyweds and those who have been married for a long time. Through this study, the author can provide valuable insights for the Mejayan Religious Affairs Office and related agencies to improve the quality of existing guidance. This is not only beneficial for married couples, but also for society as a whole, in creating more harmonious and happy families. In this study, the author has a problem with the Implementation of Law Number 16 of 2019 concerning Marriage Dispensation at the Mejayan Religious Affairs Office, Madiun Regency from an Islamic law perspective. The research approach in this thesis is a descriptive research method, namely a model in examining a group of people, an object, a state of mind or a class of events in the present. The KUA's efforts in socializing and implementing this law are key to realizing the expected changes. Islamic law seeks to balance the principles of sharia and social realities, ensuring that marriages are entered into with careful consideration and under conditions that best support the well-being of the individuals involved.